ADRB3 Gene Trp64Arg Polymorphism and Essential Hypertension: A Meta-Analysis Including 9,555 Subjects - Li, Yan-yan; Lu, Xin-zheng; Wang, Hui; Zhou, Yan-hong; Yang, Xin-xing; Geng, Hong-yu; Gong, Ge; Kim, Hyun Jun (Frontiers in Genetics, 2018)
Background: Presence of the β3-Adrenergic receptor (ADRB3) gene Trp64Arg (T64A) polymorphism may be associated with an increased susceptibility for essential hypertension (EH). A clear consensus, however, has yet to be reached. Objective and methods: To further elucidate the relationship between the ADRB3 gene Trp64Arg polymorphism and EH, a meta-analysis of 9,555 subjects aggregated from 16 individual studies was performed. The combined odds ratios (ORs) and their corresponding 95% confidence intervals (CI) were evaluated using either a random or fixed effect model. Results: We found a marginally significant association between ADRB3 gene Trp64Arg polymorphism and EH in the whole population under the additive genetic model (OR: 1.200, 95% CI: 1.00-1.43, P=0.049). Association within the Chinese subgroup, however, was significant under allelic (OR: 1.150, 95% CI: 1.002-1.320, P=0.046), dominant (OR: 1.213, 95% CI: 1.005-1.464, P=0.044), heterozygous (OR: 1.430, 95% CI:1.040-1.970, P=0.03), and additive genetic models (OR: 1.280, 95% CI: 1. 030-1.580, P=0.02). A significant association was also found in the Caucasian subgroup under allelic (OR: 1.850, 95% CI: 1. 260-2.720, P=0.002), dominant (OR: 2.004, 95% CI: 1.316-3.052, P=0.001), heterozygous (OR: 2.220, 95% CI: 1.450-3.400, P=0.0002), and additive genetic models (OR: 2.000, 95% CI: 1. 330-3.010, P=0.0009). Conclusions: The presence of the ADRB3 gene Trp64Arg polymorphism is positively associated with EH, especially in the Chinese and Caucasian population. The Arg allele carriers of ADRB3 gene Trp64Arg polymorphism may be at an increased risk for developing EH.